Prognostic and clinicopathological value of the geriatric nutritional risk index in gastric cancer: A meta-analysis of 5,834 patients - He, Liang; Li, Ying; Qu, Linlin; Zhang, Fan (Frontiers in Surgery, 2023)
Background: Recent studies have explored the prognostic value of the geriatric nutritional risk index (GNRI) in patients with gastric cancer (GC), but the results are controversial. We aimed to systemically identify the association between the GNRI and prognosis in GC using a meta-analysis. Methods: The databases of PubMed, Web of Science, Cochrane Library, and Embase were searched until September 25, 2022. Pooled hazard ratios and the corresponding 95% confidence intervals (CIs) were used to estimate the prognostic value of the GNRI in GC. Odds ratios (ORs) and 95% CIs were used to assess the correlation between the GNRI and clinicopathological characteristics of GC. Results: Ten studies including 5,834 patients with GC were included in this meta-analysis. The merged results indicated that a low pretreatment GNRI was associated with inferior overall survival (hazard ratio=1.21, 95% CI=1.12-1.30, P<0.001) and worse cancer-specific survival (hazard ratio=2.21, 95% CI=1.75-2.80, P<0.001) for GC. Moreover, a low GNRI was significantly associated with an advanced pathological stage (OR=2.27, 95% CI=1.33-3.85, P=0.003), presence of adjuvant chemotherapy (OR=1.25, 95% CI=1.01-1.55, P=0.040), and tumor location in the lower stomach (OR=1.33, 95% CI=1.06-1.65, P=0.012) in GC. However, there was no significant association between GNRI and sex, tumor differentiation, or lymph node metastasis in patients with GC. Conclusions: Our meta-analysis identified that the pretreatment GNRI level was a significant prognostic factor for patients with GC. A low GNRI is associated with worse overall survival and inferior cancer-specific survival in patients with GC.